Moderating a mean and scary world: Fear-related coping strategies in television programs for the preschool audience. - Connell, Sabrina. (2017)
Abstract: Previous research has suggested that young children primarily rely on social support and behavioral, rather than cognitive, coping strategies when managing fears of the dark and monsters. Research has also suggested that affirming reality may be less effective than other means, such as positive pretense, in helping children cope with fear. This thesis examined how preschool television programs addressed fear of the dark and fear of monsters. Both quantitative and qualitative content analyses were conducted with a sample of ten fear-related preschool programs. Results indicated that a variety of coping strategies were portrayed, with behavioral strategies portrayed more frequently than cognitive strategies. Reality affirmation was frequently presented, while positive pretense was less frequently portrayed. Most coping instances in the sample involved some form of social support. Future directions for research include further exploration of the impact such television programs have on the development of fear-related coping repertoires in young children.; Thesis (M.A.)--Tufts University, 2011.; Submitted to the Dept. of Child Development.; Advisor: Kathleen Camara.; Committee: Julie Dobrow, and Fred Rothbaum.; Keywords: Developmental Psychology, and Communication.